Oznaczenia geograficzne szansą promocji produktów regionalnych i tradycyjnych - Jasiulewicz, Anna (Geographical Indications as a Chance of Regional and Traditional Products Promotion, 2005)
The article points at the importance of the protection of designation of origin, protection of geographical indication and traditional speciality guaranteed labels as the instruments that shape the foodstuffs quality, assure their uniqueness and increase their attractiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 352-357